PENINGKATAN HASIL BELAJAR MELALUI PENERAPAN METODE PEMBELAJARAN FIQIH YANG EFEKTIF DI MADRASAH IBTIDAIYAH NEGERI 1 PASER - Nazla, Siti; Wahyuni, Sri; Adiyono, Adiyono (STIT Ibnu Rusyd Tanah Grogot, 2023)
The purpose of this study is to provide effective learning outcomes on the application of fiqh learning methods in madrasah ibtidaiyah negeri 1 paser. In learning fiqh at MIN 1 Paser, an educator applies the five methods, question and answer, demonstration, reading, drill, and games but what is often applied is the drill or practice method and the game method. The game method is usually done by educators in class. This research also focuses on the use of game method as one of the more interesting learning approaches for students. Game methods that are usually done by educators in class can help enrich learners' learning experience and motivate them to be more active in learning. The use of ice breaking as an introductory technique before learning begins. Ice breaking helps in reducing learners' anxiety and creating a conducive learning atmosphere.